1990
DOI: 10.1002/jab.770010203
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of 2‐cyanoacrylates as surgical adhesives

Abstract: To evaluate 2-cyanoacrylates as surgical adhesives, the bond strength in vivo as well as the tissue reaction was investigated using methyl-, ethyl-, isobutyl-, and ethoxyethyl-2-cyanoacrylate. In addition, their set time and spreading on blood were studied. When the 2-cyanoacrylates were applied to an incised site of rabbit skin, they could maintain the skin closure without suturing during the first week and the bond strength increased during the second week. Significant inflammatory response was observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 9 publications
1
47
0
Order By: Relevance
“…The resulting pellicle joins the adhesives like a bridge. The most important chemical characteristic of CAs is the capacity to form a quick, strong bond that progressively increases in intensity over the following 48 h 5,6 . The advantages of CA in cutaneous synthesis are widely described in the literature 7 , however, these products have been underutilized in Brazil due to high costs 6 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The resulting pellicle joins the adhesives like a bridge. The most important chemical characteristic of CAs is the capacity to form a quick, strong bond that progressively increases in intensity over the following 48 h 5,6 . The advantages of CA in cutaneous synthesis are widely described in the literature 7 , however, these products have been underutilized in Brazil due to high costs 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The most important chemical characteristic of CAs is the capacity to form a quick, strong bond that progressively increases in intensity over the following 48 h 5,6 . The advantages of CA in cutaneous synthesis are widely described in the literature 7 , however, these products have been underutilized in Brazil due to high costs 6 . Moreover, the most accessible CA form is 2-ethyl cyanoacrilate 4 (ECA), which has been not widely studied in terms of tolerance, histological reactions in different cicatrisation phases and capacity to avoid dehiscence 6,[8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 Cyanoacrylate polymer has connected the organs by the strong adhesion on wet surface of tissue, however, it has serious drawbacks to be obstructive the progress of wound healing by hard solid and also to produce formaldehyde by degradation of cyanoacrylate. 12,13 Although fibrin glue using blood coagulation systems containing fibrinogen, thrombin, factor XIII, and protease inhibitor, has been attracted as a friendly suture material for body, it has been reported on risky infection, because it originated from the blood of human and cattle. [14][15][16][17] It was reported that the chitosan membrane adheres to tissue.…”
mentioning
confidence: 99%